Prof. Lyudwik Mirzoyan’s life and activity - Hambaryan, V. V.; Akopian, A. A.
Prof. Lyudwik Mirzoyan is one of the best representatives of the first generation of Armenian astronomers who had founded Byurakan Observatory and the Byurakan direction in science. For thirty years he had been the assistant of Victor Hambartsumian at Byurakan Observatory and has a huge input in formulation of the modern understanding of star formation, thus becoming the pioneer in Armenian observational astronomy.
Keywords: Astronomy